Job satisfaction among public servants in Perlis State Secretary Office / Mazfazira Mohd Tasnuha and Syafiqah Najat Shukor - Mohd Tasnuha, Mazfazira; Shukor, Syafiqah Najat (2019)
This chapter focuses on the background of the study, which is measure the job satisfaction among public servants in Perlis State Secretary Office. The presentation of this chapter begins with the research background, followed by the problem statement, research questions, research objectives scope of the study, significant of the study, the definitions of the terms and concepts used in this study and lastly is the conclusion.